Gastropods and bivalves of commercial interest from the continental shelf of Jalisco and Colima, México - Ríos-Jara, E (2001)
The distribution and abundance with respect to depth and type of substratum of 20 species of gastropods and four species of bivalves of economic importance were examined in the continental shelf of Jalisco and Colima, México. These species were taken with net trawls at depths from 24 to 83 m in August, 1988. Most individuals and species of gastropods were collected in stations with sandy silt substratum. Bivalves were collected in sandy silt and medium sand substrata. The six most abundant species represented 81.2 % of all gastropods and bivalves collected. These species are: Cantharus pallidus, Fusinus dupetittouarsi, Ficus ventricosa, Hexaplex brassica, Harpa conoidalis and Arca pacifica.